(untitled) (The Pakistan Development Review, 1988)
Most rural populations in underdeveloped countries are poor, no matter how one defines poverty. The rural poor are neither a homogeneous group, nor is the incidence of poverty equally distributed among them. They do, however, share the underlying causes of their poverty. Landlessness (or absence of productive land) and poor prospects of employment at low wage rates are among the major factors. In some regions, the natural and physical environment exacerbates the conditions of poverty, even if the poor have reasonable entitlements to land. The prospects of improved living conditions for the rural poor depend on many factors. The major ones seem to be (a) population growth, (b) technical progress, (c) markets, and (d) public policy environment. The contribution of each of these factors is not easy to identify, because they act on the human condition in an interdependent and complex way. In most underdeveloped countries, the forces of market and government policies tend to work against the rural poor.